Siyāsah Shar'iyyah and the Politicization of Religion in the 2019 Indonesian Presidential Election - Zainuddin Zainuddin; Roni Efendi; Jamal Mirdad; Salmy Edawati Yaacob (AHKAM : Jurnal Ilmu Syariah, 2022)
The politicization of religion in general elections has been a global issue in both religious and secular countries. Since 1955 to 2019, Indonesia experienced political contests laden with religious attributes, which sparked conflicts. This research aims to analyze the relevant issues and motives associated with using religious elements in the presidential election campaign 2019. This study  is  empirical  research  and  involves  interviews  with  high-level  officials of  political  parties.  Furthermore,  the  online  mass  media,  official  blogs  of candidate  pairs  for  president  and  vice  president,  and  social  media  were employed  as  secondary  data.  Following  the  analysis,  the  result  implies  that the politicization of religion in the 2019 presidential election campaign firmly appears  amidst  the  decline  of  presidential  and  vice  presidential  candidates' religious  polarization.  The  use  of  religious  issues  in  the  campaign  yielded public  sympathy  and  antipathy,  affecting  the  electability  of  presidential and  vice  presidential  candidates.  Meanwhile,  counter-elements  contradict negative images that discredit presidential and vice presidential candidates. The motives for politicizing religion were identified as "political pragmatism" and "culturalism politics". Ideological interest was also identified as a motive but  did  not  arise  in  the  2019  presidential  election.  From  siyāsah  shar'iyyah perspective, the politicization of religion could threaten the sharia objective of  creating  social  advantage  (maṣlaḥah).  Politicization  using  religious  issues amounts  to  religious  commodification,  which  is  irrelevant  to  the  sharia objective.Keywords: politization of religion; campaign; presidential election; siyāsah shar'iyyah AbstrakPolitisasi agama dalam pemilihan umum telah menjadi isu global di banyak negara, baik negara-negara berbasis agama maupun sekuler. Indonesia telah  melaksanakan  pemilihan  umum  sejak  tahun  1955  hingga  2019  dalam prosesnya  banyak  sekali  muncul  isu-isu  keagamaan  yang  menyebabkan terjadinya konflik dan perpecahan. Penelitian ini bertujuan untuk memetakan dan menganalisis isu-isu terbaru dan motif penggunaan isu keagamaan dalam kampanye  Pilpres  2019.  Penelitian  ini  merupakan  penelitian  fenomenologis empiris. Data diperoleh dari pengurus dan anggota partai politik. Selain itu diperoleh dari media cetak, media elektronik, media online/internet seperti blok resmi  pasangan  calon  presiden-calon  wakil  presiden  dan  media  sosial.  Hasil penelitian menemukan bahwa politisasi agama dalam kampanye Pilpres 2019 semakin menguat di tengah melemahnya polarisasi agama. Isu-isu keagamaan dalam  kampanye  telah  menimbulkan  simpati  dan  antipati  publik  sehingga mempengaruhi elektabilitas pasangan calon presiden-calon wakil presiden. Di sisi  lain  isu-isu  yang  mengkonter  berusaha  menormalisasi  citra  negatif  yang dialamatkan  pada  pasangan  calon  presiden-calon  wakil  presiden.  Isu-isu  ini muncul untuk kepentingan sesaat sebagai wujud politik pragmatis, di samping politik kultural. Kepentingan ideologis tetap terbaca walaupun tidak mengemuka secara  transparan,  karena  hambatan  konstitusional.  Dalam  pandangan  siyāsah shar'iyyah, politisasi agama dapat mengancam tujuan syariat untuk mewujudkan kemashlahatan. Politisasi dengan menggunakan isu-isu keagamaan merupakan komodifikasi agama yang tidak sejalan dengan cita-cita syariat itu sendiri.Kata Kunci: politisasi agama; kampanye; pemilihan presiden; siyāsah shar'iyyah